Społeczno-gospodarczy aspekt konsolidacji sektora stoczniowego w Polsce - Romanowska, Mirela (Consolidation as a Stage of Restructuring Processes on the Example of Shipping Industry, 2005)
The interest in the shipping industry is related to its strategic relevance not only in economic but also social terms, which is the reason why it arouses considerable interest also among local authorities and the government. Its crucial role in Polish economy is reflected in its high share in total exports and a large number of transactions with business partners. The survival of the shipping industry is a precondition for that business network's further existence on the market. The paper presents the essence and stages of consolidation processes in the shipping industry.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 350-357